Agritourism Development Strategy Strawberries in Nagari Pandai Sikek Sub-District X Koto District Flatland District West Sumatra (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This study aims to determine how the strawberry (Fragaria sp.) agritourism development system is located in Tanah Datar Regency, Nagari Pandai Sikek. In addition, through direct observation and field research, researchers conducted extensive and focused research to obtain complete and precise data on the subject matter under study. The manager and the community can benefit financially from the strawberry garden (Fragaria sp.) in Jorong Koto Tinggi Nagari Pandai Sikek District X Koto Tanah Datar Regency. Since its opening, this strawberry garden attraction has continued to attract tourists. Methodology for Development of Strawberry Nursery Agrotourism (Fragaria sp.) in Sikek Nagari Pandai: 1. S-O strategy 2. S-T strategy 3. S-T strategy 4. W-O strategy 5. W-T strategy 6. W-T strategy 7. W-O strategy 8. W-T strategy 9. W-T strategy 10. W-O strategy 11. W-T strategy 12. W-T strategy W-O strategy 4. W-T strategy W-T procedure. Strawberry (Fragaria sp.) agritourism has a lot of potential for future business opportunities. Twelve alternative strategies were identified through SWOT analysis, resulting in the following prioritized order of strategies: (1) Maintain the quality of goods, (2) Distinguish strawberry seedlings and other crops, (3) Provide strawberry-handled goods in turn, (4) Select capable representatives, (5) Add offices and frameworks, (6) Advance through extension, (7) Provide instructional visits and culinary visits, (8) Assist regions and local governments, (9) Follow and maintain existing offices, (10) Implement good agricultural practices, and (11) Seek better transportation access.